Analisis Penentuan Titik Kendali Kritis dalam Proses Pengolahan Nasi Goreng Buntut Berdasarkan Prinsip HACCP di Spice Restaurant Oakwood Hotel and Residence Surabaya - Putri Kharisma Sejahtera; Niken Purwidiani; Qorry Aina; Nufimbar Susy Anindita Handayani (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the determination of Critical Control Points (CCPs) in the fried rice processing process based on the Hazard Analysis and Critical Control Point (HACCP) principles at Spice Restaurant Oakwood Hotel & Residence Surabaya. The study used a qualitative descriptive method with data collection techniques through direct observation of the processing stages, interviews with the kitchen manager and processing staff, and documentation. The analysis was carried out by compiling a flow chart, identifying biological, chemical, and physical hazards at each stage, and determining CCPs based on the HACCP principles. The research results show that the raw material receipt, storage, and preparation stages are categorized as Control Points (CP), while the cooking stage of oxtail fried rice is designated as the only Critical Control Point (CCP). The boiling, portioning, and serving stages of oxtail still require control through SOPs, personal hygiene, and cross-contamination prevention.